Reduced Antibodies and Innate Cytokine Changes in SARS-CoV-2 BNT162b2 mRNA Vaccinated Transplant Patients With Hematological Malignancies - Bergamaschi, Cristina; Pagoni, Maria; Rosati, Margherita; Angel, Matthew; Tzannou, Ifigeneia; Vlachou, Margarita; Darmani, Ismini; Ullah, Amirah; Bear, Jenifer; Devasundaram, Santhi; Burns, Robert; Baltadakis, Ioannis; et al. (Frontiers in Immunology, 2022)
Immunocompromised individuals including patients with hematological malignancies constitute a population at high risk of developing severe disease upon SARS-CoV-2 infection. Protection afforded by vaccination is frequently low and the biology leading to altered vaccine efficacy is not fully understood. A patient cohort who had received bone marrow transplantation or CAR-T cells was studied following a 2-dose BNT162b2 mRNA vaccination and compared to healthy vaccine recipients. Anti-Spike antibody and systemic innate responses were compared in the two vaccine cohorts. The patients had significantly lower SARS-CoV-2 Spike antibodies to the Wuhan strain, with proportional lower cross-recognition of Beta, Delta, and Omicron Spike-RBD proteins. Both cohorts neutralized the wildtype WA1 and Delta but not Omicron. Vaccination elicited an innate cytokine signature featuring IFN-gamma, IL-15 and IP-10/CXCL10, but most patients showed a diminished systemic cytokine response. In patients who failed to develop antibodies, the innate systemic response was dominated by IL-8 and MIP-1alpha with significant attenuation in the IFN-gamma, IL-15 and IP-10/CXCL10 signature response. Changes in IFN-gamma and IP-10/CXCL10 at priming vaccination and IFN-gamma, IL-15, IL-7 and IL-10 upon booster vaccination correlated with the Spike antibody magnitude and were predictive of successful antibody development. Overall, the patients showed heterogeneous adaptive and innate responses with lower humoral and reduced innate cytokine responses to vaccination compared to naïve vaccine recipients. The pattern of responses described offer novel prognostic approaches for potentiating the effectiveness of COVID-19 vaccination in transplant patients with hematological malignancies.